SOSIALISAI STRATEGI KOMUNIKASI BENCANA EFEKTIF GEMPA BUMI DI BALI - Ragil Noviyanti (LPPM Universitas dr. Soebandi, 2026)
Disaster communication plays a vital role in minimizing the impact of earthquakes in vulnerable regions such as Bali, Indonesia. This study aims to analyze effective disaster communication strategies implemented by local governments and stakeholders in responding to earthquake emergencies. Using a descriptive qualitative method with a case study approach, data were collected through interviews with representatives from the Regional Disaster Management Agency (BPBD), community leaders, and local residents. The research stages included identification of communication channels, message delivery patterns, and evaluation of public response during disaster events. The findings reveal that the effectiveness of disaster communication depends on multi-stakeholder coordination, the use of early warning systems, and the establishment of trusted information networks at the community level. Furthermore, public awareness and preparedness significantly increase when communication strategies are culturally adaptive and supported by consistent government engagement. The study concludes that an integrated, two-way communication system supported by technological innovation and local wisdom can enhance the effectiveness of earthquake disaster management in Bali.